Portraying reflection: the contents of student teachers' reflection on personal practical theories and practicum experience*. Issue 5 (3rd September 2017) - Maaranen, Katriina; Stenberg, Katariina
Abstract: This research focused on personal practical theories of Finnish student teachers, on how they argued for them and what they contained, and the data were analysed using Korthagen's 'onion' model of reflection (e.g. 2004). The framework of this research consists of reflection and personal practical theories (PPTs). Personal practical theories are viewed as important for a teacher's identity: they guide the teacher's work, action, and reactions before, during, and after a teaching event. Reflecting on teaching, then again, has been one of the most significant issues and focus of numerous studies for several decades. This is a case study of six elementary school student teachers, who had constructed their PPTs before the practicum. We examined their reflections using the onion model of reflection, according to which a person reflects on different levels. The data were collected by interviewing the student teachers after their final practicum. The results show that most of their reflection focused on Environment and Behaviour, so it was located mostly in the outer layers of the onion model. The categorization of the reflection also showed that Competence was the smallest category.